2018
DOI: 10.1002/stc.2279
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐layer nanotube‐based smart skin for enhanced noncontact strain sensing

Abstract: The remarkable optical properties of single-walled carbon nanotubes suggest their use as nanoscale strain sensors. To help implement this idea as a practical technology, we have devised a new dual-layer strain-sensing smart skin. A submicron thick sensing layer of dilute, individualized nanotubes in poly(9,9-di-n-octylfluorenyl-2,7-diyl) (PFO) polymer is deposited onto the substrate to be monitored and then overcoated with a transparent protective polymer layer. Subsequent substrate strains are transmitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…One of the most intriguing properties of semiconducting single-wall carbon nanotubes (SWCNTs) is their structure-specific fluorescence at short-wave infrared (SWIR) wavelengths 1,2 . This has inspired emerging applications in areas that include bioimaging 39 and optical noncontact sensing 1012 . In addition, it has been shown that SWCNTs with some types of sparse covalent doping give spectrally shifted emission arising from the trapping of mobile excitons at the defect sites.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most intriguing properties of semiconducting single-wall carbon nanotubes (SWCNTs) is their structure-specific fluorescence at short-wave infrared (SWIR) wavelengths 1,2 . This has inspired emerging applications in areas that include bioimaging 39 and optical noncontact sensing 1012 . In addition, it has been shown that SWCNTs with some types of sparse covalent doping give spectrally shifted emission arising from the trapping of mobile excitons at the defect sites.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral region from ca. 1000 to 1600 nm (often termed short-wave infrared or SWIR) is attractive for optical applications such as bioimaging, , telecommunications, and nondestructive inspection because of favorable interactions with materials. For example, SWIR expands the detection window for optical imaging in biomedical research, offering improved image contrast through lower scattering and greatly reduced tissue autofluorescence …”
mentioning
confidence: 99%
“…For example, ink made from semiconducting SWCNTs dispersed by poly(9,9‐di‐ n ‐octylfluorenyl‐2,7‐diyl) in toluene was spray‐coated on a flexible substrate and then covered with a second flexible substrate. [ 145,146 ] This bilayer “skin” is then transferred to a substrate such as a wall. Local strain induced in this bilayer skin structure by the substrate causes spectral shifts in the nanotube PL.…”
Section: Emergent Applicationsmentioning
confidence: 99%